(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Material cost contributes 50% to 60% of the total cost of the project. Thus material forms the single largest component of the total cost of the construction activities. Improper selection of suppliers leads to problems related to material price, delivery, communication, quality, availability of materials on time etc. and its adverse effect on the cost of project. Thus, there arises the need of ideal supplier for avoiding time and cost overrun. It can be possible to select the ideal supplier with the help of several supplier selection methods but these traditional methods fails to collect correct information of all the suppliers also it takes more time to collect such information manually. With the help of data base management tools the collection of required supplier data like personal details, cost of materials, quantity, quality, delivery address, location, discount, transportation facility, communication facility etc. would be less or no time consuming. Hence GIS is a powerful set of tools for collecting, storing and quantifying all data of all suppliers and easily screen all suppliers in very short time. This paper suggest that the proposed Arc GIS 10.0 based methodology may replace the manual methods to extract supplier’s information from the available data base , locate location of suppliers and ideal suppliers by developing queries in very short time.